Macroeconomic Determinants of Bangladesh’s Foreign Exchange Reserves: Evidence from Time Series Analysis - Suman, Shihab Uddin; Shanta, Mahbuba Akter (Asian Business Review, 2025)
There is no denying that an optimal level of foreign exchange reserves is crucial for maintaining macroeconomic stability and achieving steady economic growth. Additionally, it can serve as a development tool by financing import payments and supporting essential development spending, making it a symbol of the country's economic sustainability. This study utilizes monthly data from January 2008 to July 2022, sourced from the Bangladesh Bank, the central bank of Bangladesh, to examine the determinants of Bangladesh's foreign exchange reserves. A standard time series approach was used, which involved testing for stationarity and selecting the appropriate lag length before applying the Johansen cointegration test to identify the presence and rank of cointegrating relationships. This study identified multiple cointegrating equations and, therefore, employed the Vector Error Correction Model (VECM) to investigate the long-term relationships among the variables. The results indicated that exports, remittances, and foreign direct investment have a positive influence on foreign exchange reserves, while imports and the exchange rate have a negative impact. Short-term dynamics and the error correction term (ECT) were also analyzed to demonstrate adjustment processes. Following the econometric analysis, diagnostic tests, including autocorrelation, normality, and stability tests, were performed. The results showed that autocorrelation and stability tests were satisfactory; however, only imports followed a normal distribution, as confirmed by the normality test. Based on these findings, this study recommends several policy measures to help Bangladesh maintain an optimal level of foreign exchange reserves. Since exports, remittances, and foreign direct investment positively affect Bangladesh’s foreign exchange reserves, efforts should focus on expanding these sectors through export diversification, improved support for remitters, and providing additional facilities or incentives to attract foreign direct investment.JEL Classification Code: G 21